REWRITING THE OFFICIAL VERSION OF HISTORY: A STUDY OF DAN BROWN’S THE DA VINCI CODE (International Journal of Food and Nutritional Sciences, 2022)
Literature includes art, history, and music in the form of writing to pass the human culture, practice, and events of the past and present to the next generation. History is one of the most referred terms in the world by which every race of humanity tries to find its unique lifestyle through documented events. In fiction, writers take on histories in many ways to reexamine or endorse the recorded events of the past with their own perspectives. The Da Vinci Code approaches the official version of history with a different dimension that creates new history for the official version of history and questions the credibility of the existing history. The study focuses on the Holy Grail, The Last Supper, the Merovingian dynasty, Mary Magdalene, The Priory of Sion and the pentacle in The Da Vinci Code. Brown’s interpretations for the Holy Grail and the pentacle shake the rudimentary faith in the Church and the alternative history of both leads to a spiritual as well as historical discourse in and out of literary writings.